2001
DOI: 10.1007/bf02234322
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of HIV-positive patients with anal squamous cell carcinoma

Abstract: HIV-positive patients with in situ carcinomas present at an earlier age than those with infiltrating lesions. In situ patients with CD4 counts as low as 105 cells/ml do well with local excision. A low CD4 count at diagnosis without highly active antiretroviral therapy predicts a poor prognosis. Because these patients appear to succumb to their HIV status and not the anal disease, anal squamous cell carcinoma should be included with cervical squamous cell carcinoma as an AIDS-defining illness. HIV-positive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 32 publications
2
39
0
4
Order By: Relevance
“…There was a discrepancy in the number of patients with SCC of the anus in the HIV positive cohort (68%) compared to the number of patients in the HIV negative cohort (31%). This supports past findings that HIV positive individuals have a higher risk of developing anal SCC than HIV negative individuals [4,5,[15][16][17].…”
Section: Discussionsupporting
confidence: 91%
“…There was a discrepancy in the number of patients with SCC of the anus in the HIV positive cohort (68%) compared to the number of patients in the HIV negative cohort (31%). This supports past findings that HIV positive individuals have a higher risk of developing anal SCC than HIV negative individuals [4,5,[15][16][17].…”
Section: Discussionsupporting
confidence: 91%
“…A second series by Place and colleagues reported simi- a AIDS is defined either by CD4 count Յ200/mmlar findings [41]. Those authors reported on 14 HIV-positive patients treated for squamous cell carcinoma of the anus between 1980 and 1999.…”
Section: Treatment Of Hiv-positive Patientsmentioning
confidence: 97%
“…Given the impact of chemoradiation therapy on the immune system, investigators have wondered if the greater toxicity observed in these patients is related to the impact that HIV infection has on the immune system. Several series have attempted to address this question by evaluating outcomes in the context of CD4 count (Table 4) [32,41]. Hoffman and colleagues reported on a series of 18 consecutive HIV-positive patients treated at University of California at San Francisco between 1991 and 1997 [32].…”
Section: Treatment Of Hiv-positive Patientsmentioning
confidence: 99%
“…5,18,20,21 Entre os HIV-positivos, variou entre 20 e 100%, 9,19,22,23 mas não há relato quanto ao grau de imunodepressão e as casuísticas são pequenas. Todavia, naqueles que receberam o esquema de drogas anti-retrovirais, 24 o número de linfócitos T CD4+ aumentou, 16 com efeito positivo no prognóstico, 22 sugerindo melhora da imunidade e controle da doença.…”
unclassified
“…9,16 A contagem sérica baixa de linfócitos T CD4 prediz mau prognóstico. 22,23 A redução do tamanho do campo radioterápico pode diminuir a quantidade de complicações imediatas, mas pode proporcionar maior recidiva da doença, fato que pode ocorrer em até 20% dos casos. 28 A toxicidade também pode melhorar se a MTMC não for administrada, mas há maior probabilidade de recidiva na sua ausência (73% versus 51%).…”
unclassified